2017
DOI: 10.5194/bg-14-4061-2017
|View full text |Cite
|
Sign up to set email alerts
|

Does denitrification occur within porous carbonate sand grains?

Abstract: Abstract. Permeable carbonate sands form a major habitat type on coral reefs and play a major role in organic matter recycling. Nitrogen cycling within these sediments is likely to play a major role in coral reef productivity, yet it remains poorly studied. Here, we used flow-through reactors and stirred reactors to quantify potential rates of denitrification and the dependence of denitrification on oxygen concentrations in permeable carbonate sands at three sites on Heron Island, Australia. Our results showed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Coarse-grained sediments with higher oxygen penetration depths may exhibit higher nitrification rates, and an associated increase in nitrate availability will fuel denitrification. Sediment type and oxygen conditions can be key drivers for denitrification [64].…”
Section: Discussionmentioning
confidence: 99%
“…Coarse-grained sediments with higher oxygen penetration depths may exhibit higher nitrification rates, and an associated increase in nitrate availability will fuel denitrification. Sediment type and oxygen conditions can be key drivers for denitrification [64].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies applying the IPT to permeable sediments have been largely carried out in dynamic intertidal environments where advection has a large impact on sediment processes. Studies investigating N cycling in intertidal sandy sediments have used flow-through sediment columns (Rao et al 2007;Evrard et al 2012), percolation techniques (Gao et al 2010;Marchant et al 2014Marchant et al , 2016, experimental chamber simulations (Cook et al 2006), stirred reactors (Cook et al 2017), push-pull methods (Erler et al 2014), flume experiments (Kessler et al 2012), in situ advective chambers , and various modeling techniques (Cook et al 2006;Kessler et al 2012Kessler et al , 2014aNeumann et al 2017) to account for advective solute exchange. These studies have demonstrated the great importance of this sediment type for benthic N turnover and loss through N 2 (Eyre et al 2008Gao et al 2012;Marchant et al 2016) and/or N 2 O production (Marchant et al 2018).…”
Section: Permeable Sedimentmentioning
confidence: 99%
“…Anoxic microenvironments have been observed to occupy no more than 10% of the pore space, are generally smaller than a few millimeters, and persist from hours to days. 4,10,29 Despite the small portion of pore volume occupied, anoxic microenvironments are nowadays considered fundamental to explain the dynamics of many macroscale ecological processes such as element cycling (e.g., soil carbon stabilization 13 and sulfur reduction and precipitation 30 ), greenhouse gas production (e.g., methanogenesis 31,32 and NO x emissions 17,29,33 ), heavy metal mobilization, 34,35 and natural attenuation of recalcitrant pollutants that accumulate in groundwater. 14,15 Yet, a quantitative understanding and predictability of anoxic microenvironment formation in oxic subsurface porous environments are missing due to major methodological limitations.…”
Section: ■ Introductionmentioning
confidence: 99%